Aerosol‐Cloud Interactions Near Cloud Base Deteriorating the Haze Pollution in East China - Ximeng Qi; Caijun Zhu; Liangduo Chen; Xuguang Chi; Jiaping Wang; Guangdong Niu; Shiyi Lai; Wei Nie; Yannian Zhu; Xin Huang; Tom V. Kokkonen; Tuukka Petäjä; et al. (Geophysical Research Letters)
Abstract Atmospheric aerosols not only cause severe haze pollution, but also affect climate through changes in cloud properties. However, during the haze pollution, aerosol‐cloud interactions are not well understood due to a lack of in situ observations. In this study, we conducted simultaneous observations of cloud droplet and particle number size distribution, together with supporting atmospheric parameters, from ground to cloud base in East China using a high‐payload tethered airship. We found that high concentrations of aerosols and cloud condensation nuclei were constrained below cloud, leading to the pronounced “Twomey effect” near the cloud base. The cloud inhibited the pollutants dispersion by reducing surface heat flux and thus deteriorated the near‐surface haze pollution. Satellite retrievals matched well with the in situ observations for low stratus clouds, while were insufficient to quantify aerosol‐cloud interactions for other cases. Our results highlight the importance to combine in situ vertical and satellite observations to quantify the aerosol‐cloud interactions.